Adjuvant chemoradiation for gastric carcinoma: State of the art and perspectives. (March 2018) - Schernberg, A.; Rivin del Campo, E.; Rousseau, B.; Matzinger, O.; Loi, M.; Maingon, P.; Huguet, F.
Highlights: Debates persist between the superiority of perioperative chemotherapy or adjuvant chemoradiotherapy in the management of gastric adenocarcinoma. This review is to synthesize current knowledge about adjuvant chemoradiotherapy. It will also present ongoing trials. Abstract: An estimated 990, 000 new cases of gastric cancer are diagnosed worldwide each year. Surgical excision, the only chance for prolonged survival, is feasible in about 20% of cases. Even after surgery, the median survival is limited to 12 to 20 months due to the frequency of locoregional and/or metastatic recurrences. This led to clinical trials associating surgery with neoadjuvant or adjuvant treatments to improve tumor control and patient survival. The most studied modalities are perioperative chemotherapy and adjuvant chemoradiotherapy. To date, evidence has shown a survival benefit for postoperative chemoradiotherapy and for perioperative chemotherapy. Phase III trials are ongoing to compare these two modalities. The aim of this review is to synthesize current knowledge about adjuvant chemoradiotherapy in the management of gastric adenocarcinoma, and to consider its prospects by integrating modern radiotherapy techniques.